Diversification and Germ-Line Determination Revisited: Linking Developmental Mechanism with Species Richness - Crother, Brian I.; White, Mary E.; Johnson, Andrew D. (Frontiers in Ecology and Evolution, 2016)
Abstract.– Background: Explanations for asymmetric patterns of diversification continue to challenge paleontologists and neontologists with competing hypotheses within genetic-development and ecological frameworks. In 1988, a hypothesis was proposed that tied a primordial germ cell (PGC) determination mechanism to clade (phyla) diversification. Two general mechanisms for PGC determination are recognized: one is termed induced because induction signals are required for the production of primordial germ cells. The other mechanism is cell-autonomous, i.e. determinative, because the cells that develop in response to specific cytoplasmic determinants in the oocyte are pre-destined to become PGCs. We revisited the hypothesis and analyzed phyla diversity with germ cell determination mechanisms and examined sister clade asymmetry. Results: After 25 years of additional data accumulation, the hypothesis that high levels of species diversification are associated with the induced mode is falsified, with the determinative mode revealed as associated with higher rates of diversification. The greater species numbers are significantly associated (ANOVA p>0.003) with the determinative mode. Analysis with appropriate sister clades is unanimous in showing the clade with the determinative mode has a significantly greater number of species relative to its induced sister clade . Conclusions: The primordial germ cell determination mechanism hypothesis explains asymmetrical species diversity and morphological disparity at the phylum level. We argue that the determinative mode of primordial germ cell determination is a constraint release that has enhanced evolvability and increased rates of speciation and morphological disparity among clades. Knowledge of the mechanism for extant theropods allows speculation that its sister clade, the Sauropodomorpha would have exhibited the induced mode. Results: After 25 years of additional data accumulation, the hypothesis that high levels of species diversification are associated with the induced mode is falsified, with the determinative mode revealed as associated with higher rates of diversification. The greater species numbers are significantly associated (ANOVA p>0.003) with the determinative mode. Analysis with appropriate sister clades is unanimous in showing the clade with the determinative mode has a significantly greater number of species relative to its induced sister clade . Conclusions: The primordial germ cell determination mechanism hypothesis explains asymmetrical species diversity and morphological disparity at